Social Conceptions of Time
XVII, 266 p.
Keywords: This book is concerned with the significance of time in work and everyday life. The contributors are among the foremost authorities in the field, and their up-to-date contributions consider the changing social meanings that time has in work, leisure and everyday routines. Together they provide a combination of theoretical and empirically-based approaches that reveal the social significance of time in all aspects of everyday lives.